Championship gymnastics: Biomechanical techniques for shaping winners - George, G. S. (Wellness Press, 2010)
Championship Gymnastics represents an entirely new approach to the study and understanding of gymnastics movement. It is the only textbook on the market that bridges the gap between theory and practice. Whether you are a gymnastics performer, teacher, coach, or even a judge, this textbook seamlessly weaves together the "science" of biomechanics with the "art" of gymnastics movement.